2010
DOI: 10.1161/atvbaha.110.212654
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin-3′-Monoxime Blocks Vascular Smooth Muscle Cell Proliferation by Inhibition of Signal Transducer and Activator of Transcription 3 Signaling and Reduces Neointima Formation In Vivo

Abstract: Objective-Our goal was to examine the influence of indirubin-3Ј-monoxime (I3MO), a natural product-derived cyclin-dependent kinase inhibitor, on vascular smooth muscle cell (VSMC) proliferation in vitro, experimentally induced neointima formation in vivo, and related cell signaling pathways. Methods and Results-I3MO dose-dependently inhibited platelet-derived growth factor (PDGF)-BB-induced VSMC proliferation by arresting cells in the G 0 /G 1 phase of the cell cycle as assessed by 5-bromo-2Ј-deoxyuridine inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…I3M has been shown to have a broad spectrum of anti-tumorigenic activities in many human cancer cells [12]. In this study, we confirmed that I3M possesses a number of anti-tumorigenic activities in vitro , and we identified a novel anti-tumorigenic role for I3M in vivo .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…I3M has been shown to have a broad spectrum of anti-tumorigenic activities in many human cancer cells [12]. In this study, we confirmed that I3M possesses a number of anti-tumorigenic activities in vitro , and we identified a novel anti-tumorigenic role for I3M in vivo .…”
Section: Discussionsupporting
confidence: 75%
“…Whereas indirubin itself has poor solubility, a low absorption rate, and significant gastrointestinal toxicity, synthetic indirubin-3′-monoxime (I3M) has better pharmacological properties and reduced toxicity. Furthermore, compared with indirubin, I3M inhibits many additional protein kinases as well as STAT3 signaling, and it has been shown to have anti-proliferative effects in vascular smooth muscle cells [10][12]. Recently, Indirubin-3′-oxime also have been reported induces mitochondrial dysfunction and triggers growth inhibition and cell cycle arrest in human neuroblastoma cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that the small molecule indirubin-3′-monoxime (I3MO) inhibits VSMC proliferation induced by PDGF in vitro and reduces vessel narrowing in vivo (1). The antiproliferative effect of I3MO, a derivate of the naturally occurring compound indirubin used in traditional Chinese medicine against cancer (2), was linked with the selective inhibition of signal transducer and activator of transcription 3 (STAT3).…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 phosphorylation at Tyr 705 and activation seem to be pivotal for VSMC proliferation (3, 4). Other PDGF-activated mitogenic kinases, like Akt and ERK1/2, were not influenced by I3MO (1). How I3MO provokes this selective action has, however, not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel (taxol) was used as a reference compound, and inhibited the proliferation of VSMC and HUVECtert with IC 50 = 108 nM and 4 nM, respectively [46]. 5-bromo-2′-deoxyuridine (BrdU) incorporation assay: Quiescent VSMCs were pre-treated for 30 min with compound, or vehicle (0.1 % DMSO) as indicated and stimulated with PDGF (20 ng/mL) for 2 h. Then BrdU was added to estimate de novo DNA synthesis in VSMCs [47][48][49]. 22 h later, the BrdU incorporation was quantified according to the manufacturerʼs instructions (Roche Diagnostics).…”
Section: Bioactivity Evaluationmentioning
confidence: 99%